Addressing supplier sustainability misconducts: response strategies to nonmarket stakeholder contentions. Issue 8 (18th May 2021) - Hajmohammad, Sara; Shevchenko, Anton; Vachon, Stephan
Abstract : Purpose: Firms are increasingly accountable for their suppliers' social and environmental practices. Nonmarket stakeholders nowadays do not hesitate to confront buying firms for their suppliers' misconducts by mobilizing demonstrations, social media campaigns and boycotts. This paper aims to develop a typology of response strategies by targeted firms when they face such contentions and to empirically investigate why these strategies vary among those firms. Design/methodology/approach: Drawing on social movement and stakeholder salience theories, the authors develop a set of hypotheses linking their typology of four response strategies to three key contextual factors – nonmarket stakeholder salience, nonmarket stakeholder ideology and the target firm reputation – and examine them using a vignette-based experiment methodology. Findings: The results suggest that nonmarket stakeholder salience significantly impacts the nature of response (reject or concede), whereas the nonmarket stakeholder ideology is significantly related to the intensity of response (trivial or vigorous). Interestingly, the firms' reputation was found to have no significant effect on their response strategy when they faced stakeholder contentions. Originality/value: This paper adds both theoretical and methodological value to the existing literature. Theoretically, the study develops and tests a comprehensive typology of response strategies to nonmarket stakeholder contentions. Methodologically, this study is original in leveraging a vignette-based experiment that allows establishing causal factors of response strategies following a supplier sustainability misconduct.